2017
DOI: 10.1007/s10696-017-9285-7
|View full text |Cite
|
Sign up to set email alerts
|

The Cargo Fare Class Mix problem for an intermodal corridor: revenue management in synchromodal container transportation

Abstract: The intermodal hinterland transportation of maritime containers is under pressure from port authorities and shippers to achieve a more integrated, efficient network operation. Current optimisation methods in literature yield limited results in practice, though, as the transportation product structure limits the flexibility to optimise network logistics. Synchromodality aims to overcome this by a new product structure based on differentiation in price and lead time. Each product is considered as a fare class wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 17 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…[13] assess service and transfer selection for different freight within a synchromodal network under uncertain demand by using a look-ahead approach. The revenue management aspect of synchromodality is addressed by [16] who focus on the cargo fare class mix problem to demonstrate that booking limits for differentiated fare classes at a tactical level lead to increased revenue. Synchromodal benefits from a supply chain perspective are studies by [30] who demonstrate an increase in intermodal rail transport share when taking into account more holistic supply chain impacts.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] assess service and transfer selection for different freight within a synchromodal network under uncertain demand by using a look-ahead approach. The revenue management aspect of synchromodality is addressed by [16] who focus on the cargo fare class mix problem to demonstrate that booking limits for differentiated fare classes at a tactical level lead to increased revenue. Synchromodal benefits from a supply chain perspective are studies by [30] who demonstrate an increase in intermodal rail transport share when taking into account more holistic supply chain impacts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the synchromodal concept needs more quantification to demonstrate the benefits of having a dynamic and flexible network of services. In this regard, there is only a limited number of quantitative studies [12][13][14][15][16] and our paper is to contribute to this body of literature by using a computational approach. The motivation behind this is that analytical approaches assess freight systems from a central perspective, considering how the solution can work in the most efficient way for the given centralized system or a corridor, but little has been done from a decentralized perspective where the needs and objectives of cargo owners can be considered.…”
Section: Introductionmentioning
confidence: 99%
“…In general, products in transportation context are defined by their price, lead time, and resulting service level. In contrast to traditional pricing mechanisms, van Riessen et al [53] and van Riessen et al [54] designed new pricing strategies that consider the synchromodal characteristics of a-modal booking and real-time switching.…”
Section: Taxonomy Of Quantitative Papersmentioning
confidence: 99%
“…The study aims to show that a significant revenue increase may be achieved by considering the tactical limits on all fare classes, as opposed to traditional approaches of limiting only the lower priced class. This work is further pursued in [52] by considering a framework to distinguish between different variants of the Cargo Fare Class Mix problem. The authors demonstrated, within an intermodal case study, that significant revenue potential can indeed be gained by setting limits on each fare class, thereby outperforming existing fare class mix policies.…”
Section: Operational Levelmentioning
confidence: 99%